Spinal cord protothecosis causing paraparesis in a dog. (July 2022) - Asiag, Nimrod; Lapid, Roi; Aizenberg, Zahi; Baneth, Gad; Nachum-Biala, Yaarit; Leszkowicz-Mazuz, Monica; Yasur-Landau, Daniel; Chai, Orit; Aroch, Itamar; Shamir, Merav H.
Protothecosis, an infectious disease caused by the green algae Prototheca zopfii and P. wickerhamii, occurs sporadically in domestic animals and humans. Diagnosis of CNS protothecosis is based on neurologic signs that indicate multifocal nervous system lesions and that follow a period of chronic diarrhea and weight loss, cytologic observation of algae in fecal culture or histopathology, and detection of the agent by PCR assay of infected tissues. Here, we report a case of a paraparetic dog with CNS protothecosis that was diagnosed definitively antemortem using CSF cytology, PCR, and DNA sequencing. A 4-y-old mixed-breed dog developed progressive paraparesis that followed weight loss and diarrhea. CSF analysis revealed marked eosinophilic pleocytosis. Prototheca organisms were detected by microscopic examination of the CSF, and speciated as P. zopfii by CSF PCR and DNA sequencing. Other possible causes of paraparesis were ruled out using computed tomography, serology, and CSF PCR. The dog's condition deteriorated despite treatment, developing forebrain and central vestibular system clinical signs, and it was euthanized at the owner's request. Postmortem examination was declined. Our findings indicate that when CNS protothecosis is suspected, antemortem diagnosis can be made using CSF analysis and a PCR assay.